Characteristics of the exine and aperture of pollen grains of Eriosema and Rhynchosia (Leguminosae – Papilionoideae – Phaseoleae). Issue 4 (4th July 2019) - Oliveira, Ana Carla Da Silva; De Borges, Ricardo Landim Bormann; Perez, Ana Paula Fortuna; Lewis, Gwilym Peter; Silva, Juliana Santos
Abstract: The genera Eriosema and Rhynchosia, which comprise approximately 150 and 230 species, respectively, belong to the tribe Phaseoleae and to the subtribe Cajaninae. The pollen morphology of 49 species of Eriosema and 13 of Rhynchosia were studied using scanning electron microscopy to identify diagnostic characteristics that could aid in the taxonomic circumscription of those genera. The pollen grains analysed were obtained from specimens deposited in the BOTU, CEPEC, IPA, HRB, HUEFS, OUPR, P, S, UFC, and UFRJ herbaria. The species studied demonstrated that the pollen grains dispersed in monads, are isopolar or heteropolar, triporate or tricolporate, angulaperturate; with the endo-aperture membrane generally psilate and the exine largely reticulate heterobrocate, except for R. claussenii which is microreticulate. We discuss these diverse characteristics, including the ornamentation of the endo-aperture membrane and the margins of the apertures and reticula, to obtain information that possibly could be used to differentiate between the two genera. Although this proved not to be possible using pollen, because many characters overlap between the two genera, nevertheless some species display unique, taxonomically useful, characters, such as R. platyphylla which has an apocolpium in the shape of a 'Y', E. bauchiense with a verrucate exine ornamentation, and E. benthamianum with fossulate lumina. Additionally, two pollen types were identified in Eriosema, one group of species with 3-porate pollen grains and the other composed of species with 3-colporate grains.